2010
DOI: 10.1007/s10546-010-9490-3
|View full text |Cite
|
Sign up to set email alerts
|

Wind Conditions in Idealized Building Clusters: Macroscopic Simulations Using a Porous Turbulence Model

Abstract: Simulating turbulent flows in a city of many thousands of buildings using general high-resolution microscopic simulations requires a grid number that is beyond present computer resources. We thus regard a city as porous media and divide the whole hybrid domain into a porous city region and a clear fluid region, which are represented by a macroscopic k-ε model. Some microscopic information is neglected by the volume-averaging technique in the porous city to reduce the calculation load. A single domain approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Compared to wind tunnel data, the standard k-ε model with present grid arrangements can provide results of mean flows u(z) in good agreement with wind tunnel data, but does a little worse at predicting k(z) and can only predict the shape of vertical profile well. Such findings are similar with the same CFD validation studies the literature [23,[51][52][53]. In addition, CFD results with the fine grid are only slightly different from those with the present medium grid.…”
Section: Evaluation Of Cfd Simulations Using Wind Tunnel Datasupporting
confidence: 91%
See 2 more Smart Citations
“…Compared to wind tunnel data, the standard k-ε model with present grid arrangements can provide results of mean flows u(z) in good agreement with wind tunnel data, but does a little worse at predicting k(z) and can only predict the shape of vertical profile well. Such findings are similar with the same CFD validation studies the literature [23,[51][52][53]. In addition, CFD results with the fine grid are only slightly different from those with the present medium grid.…”
Section: Evaluation Of Cfd Simulations Using Wind Tunnel Datasupporting
confidence: 91%
“…At the domain inlet, the measured power-law profile of time-averaged (or mean) velocity U 0 (z) in the upstream free flow is adopted (see Equation (1a)) (Brown et al [51]). Moreover, the vertical profiles of turbulent kinetic energy k(z) and its dissipation rate (ε) at the domain inlet are calculated by Equations (1b) and (1c) [23,[51][52][53]: 11-column cubic building array with a parallel approaching wind. Building width (B), building height (H), and street width (W) are the same (B = H = W = 15 cm, H/W = 1, building packing densities λp = λf = 0.25, Lx = 13H, Ly = 21H).…”
Section: Model Description In the Cfd Validation Casementioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the computational load, only half of this column was considered (see Fig. 1a) [44,45]. Fig.…”
Section: Flow Set-up In the Cfd Validation Casementioning
confidence: 99%
“…Influential factors such as building morphology, canyon aspect ratio, ambient wind speed and direction were intensively studied. Hang et al [6][7][8] investigated the effect of geometry morphology on street canyon ventilation by varying aspect ratio, length and building packing density. They found that lowering aspect ratios or increasing street lengths may enhance the pollutant removal.…”
Section: Introductionmentioning
confidence: 99%